Usability and Accessibility Considerations as an Approach of Geoportals Improvement - Jazi, Sharmine Tatenda (Univerzita Pardubice, 2024)
The thesis focuses on the usability and accessibility considerations as an approach of geoportals improvement. The aim of this thesis is to examine how usability and accessibility concerns can support geoportals improvement, stressing the significance of user-centred design principles and accessibility standards. The study evaluated two web-GIS applications, Lithuania and Estonia, using heuristic assessment. The assessment involved experts examining the systems against predefined usability principles. The results showed significant differences between the two applications. Estonia had superior usability, with a more flexible scalebar feature, while Lithuania had a routing feature. Both applications had shortcomings in legend presentation, with Estonia having a broader range of layers and Lithuania's orthophoto layer offering up-to-date imagery.
Keywords: heuristic assessment; usability; accessibility; web-based gis; spatial data; heuristické hodnocení; použitelnost; dostupnost; webový gis; prostorová data